Tenure and Promotion Experiences of Music Teacher Educators: A Mixed-Methods Study. Issue 2 (February 2018) - Pellegrino, Kristen; Conway, Colleen M.; Millican, J. Si
To examine music education faculty members' promotion and tenure experiences, we interviewed ( N = 9) and surveyed ( N = 124) music teacher educators (MTEs) who were pretenure or tenured within the past 3 years. Findings highlighted MTE's perceptions of evaluative criteria and standards, mentoring programs and experiences, professional identity, and work-life balance. We found that MTEs valued three aspects of their professional identity: teacher educator, researcher, and musician, although most reported that music activities did not count as scholarly activities. We also found that MTEs need multiple mentors: someone familiar with institutional tenure policy and expectations and MTEs within and/or outside of the same institution. MTE survey respondents (70%) reported feeling stress related to the tenure process. Male respondents were more likely to feel satisfied (63%) with the balance of teaching, research, and service than female respondents (33%), and more likely to feel satisfied with the balance achieved between personal life and professional life (57%) than their female counterparts (36%).